Design and implementation of a Socioconstructivist Model of Collaborative Learning Design (SMC-LD) dedicated to distance learning - EL MHOUTI, Abderrahim; NASSEH, Azeddine NASSEH; ERRADI, Mohamed (International Journal of Computer Sciences and Engineering, 2014)
Today, the use of web technologies in education allows envisaging new learning forms, giving a preponderant place to the social dimension. However, with the emergence of these new orientations, are also developed difficulties in implementing pedagogical contents adapted to this new type of learning (collaborative, cooperative, etc.). This work is at the heart of this issue. It seeks to find conceptual and computer solutions, both at the pedagogical and technical levels, for computer modeling of pedagogical knowledge, which should be in adequacy with current learning practices. It gives itself as main objective to develop a reference model for production of distance learning contents adapted to the socioconstructivist learning context. Thus, this work proposes to develop a Socioconstructivist Model of Collaborative Learning Design (SMC-LD) of distance learning contents. In this model, the process of content development is based on socioconstructivist approach and focuses on two main aspects of production of learning content: "design" and "development". At the level "design", SMC-LD suggests a collaborative design process based on the concept of life cycle. At the level "development", SMC-LD proposes a process for educational modeling, upstream of SCORM and IMS-LD standards, describing pedagogical content using scenarios and activities. The modeling process is facilitated by an author tool to produce interoperable and reusable learning objects. To implement the proposed approach, XML and Java technologies were used.